PEACE SUSTAINABILITY IN MINING CONFLICT RESOLUTION IN SOUTHEAST SULAWESI IN REALIZING NATIONAL SECURITY - Pujo Widodo; Arifuddin Uksan; Achmed Sukendro (International Journal of Social Science, 2023)
There are several aspects that show weak coordination between the Regional Government of Southeast Sulawesi and the Central Government in dealing with mining conflicts in Southeast Sulawesi. Thus, it takes a legality and agency that specifically works to achieve peace in support of National Security, because peace is one of the goals in the Sustainable Development Goals. This study aims to analyze the sustainability of peace in mining conflict resolution in Southeast Sulawesi in realizing national security. This study uses a qualitative method. Data were obtained from designated informants which were then analyzed using qualitative analysis techniques. The results of the study show that Southeast Sulawesi Province has been prepared to implement the goals of sustainable peace since 2021. In relation to the objectivity of peace, the National and Regional Working Groups have formulated a matrix to achieve peace. This can be seen from the alignment of the National Long-Term and Medium-Term Development Plans and the Regional Long-Term and Medium-Term Development Plans to the implementation of the distribution of allocations for the State Expenditure Budget and the Regional Expenditure Budget